THE PORTRAYAL OF POWER AND AUTHORITY IN ELYSIUM FILM - Fahmi, Siti Mutiara; Astuti, Anjar Dwi; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This study discusses the portrayal of power and authority based on the order of plot in Elysium film. There are two theories used in this study: Dahrendorf’s power and authority and Reaske’s plot. The research design of this study was qualitative content analysis. The data of this study were taken from Elysium film in the form of dialogues related to the portrayal of power and authority. This study finds out that the portrayal of power and authority is divided based on the plot order of Elysium film: rising actions, climax, and resolution. Power is portrayed through the representative of Earth citizens who decide to work together. Meanwhile, authority is portrayed through the representative of Elysium citizens who decide to kill each other in taking control of Elysium. This study concludes that the representatives of power stand as the winner of the conflict by eradicating the discrimination policy of the previous Elysium that is controlled by authority and building the new Elysium without discrimination against the Earth citizens.Keywords: plot, power, authority, film